La psychanalyse en Espagne : un bilan historiographique - Anne-Cécile Druet (Mélanges de la Casa de Velázquez, 2007)
This article reviews contemporary research into the history of psychoanalysis in Spain. Such studies, which began to appear regularly during the transition period, have come to make up a considerable body, thanks in particular to the work of historians of psychiatry and psychology, and of psychoanalysts themselves. By analysing the most important studies published on the subject, we are able to identify the characteristics of each one and examine the points in common and the differences between the various authors’ different approaches. In this way we can identify several historiographic trends, of which those emerging from within the psychoanalytical movement itself are of special interest for what they reveal about the way in which the different groups write their own history. In the same way it is possible to review historical issues or periods which have been studied in depth, and likewise ones that could potentially contribute something new to the historiography of psychoanalysis in Spain today.